Pemanfaatan limbah tebu dan agen hayati bagi peningkatan kualitas beras - Padmini, Oktavia; Wuryani, Sri; Brotodjojo, Rukmowati (UNIVERSITAS PEMBANGUNAN NASIONAL â€VETERANâ€ YOGYAKARTA, 2014)
The purpose of this study was to examine the effectof boiler ash which is a waste of sugar industry and liquid organic fertilizer (LOF) to improve the quality of rice. Experiments were set up using split plot and arranged in completely randomized design, with three replicates. Main plots were composed of inorganic fertilizers on 2 levels, namely: 100% farmerâ€™s dose and 50% farmerâ€™s dose plus boiler ash 10 tons/ha. Sub plots was spraying frequency of LOF